Degradasi Budaya Modero (Studi Kasus Masyarakat Desa Lasunapa Kecamatan Duruka Kabupaten Muna) - Muhammad Nawir (JED (Jurnal Etika Demokrasi), 2017)
The main problem in this research is the degradation of modero culture arising from the presence of modernization and globalization in the life of society and the lack of public role to study the culture. This research aims to find out the preses of Modero culture degradation in Lasunapa Village of Duruka Sub-district of Muna District, impact of Modero culture degradation for Lasunapa Village of Duruka Sub-district of Muna District and role and function of Modero culture so it must be maintained. This type of research is descriptive qualitative research using data collection techniques through obeservation, interview, and documentation. This analysis is done by compiling and reducing data, displaying data concluded from various parties and providing verification to conclude. Based on the result of the research, it can be concluded that (1) Modero degradation process that happened in Lasunapa Village of Duruka Subdistrict of Muna Regency started from the new culture in society so that there was cultural mixing. (2) the negative impact of Modero's cultural degradation is the loss of the social values embodied in Modero's culture. while the positive impact of Modero's cultural degradation is that people can learn about various cultures in Indonesia. (3) the role and function of culture for the people of Desa Lasunapa sure besides can increase social solidarity among society also can increase good social interction among society.Keywords: Degradation, Culture, Madero